Whiteflies on Landscape Ornamentals - Eileen A. Buss (EDIS)
Whiteflies are common pests on many ornamental plants. Some of the most economically important species in Florida are the silverleaf whitefly, fig or ficus whitefly, citrus whitefly, and the rugose spiraling whitefly. The most frequently attacked plants include allamanda, avocado, chinaberry, citrus, fig, fringe tree, gardenia, gumbo limbo, ligustrum, mango, various palms, persimmon, viburnum, and many annuals. This 4-page fact sheet was written by E. A. Buss and published by the UF Department of Entomology and Nematology, March 2013.